Caryophylliidae (Scleractinia) from the Colombian Caribbean - Reyes, Javier; Santodomingo, Nadiezhda; Cairns, Stephen (Zootaxa, 2009)
The family Caryophylliidae comprises the highest diversity of hard corals (Order Scleractinia), represented by more than 300 species around the world. More than 90% are non-symbiotic species (azooxanthellate), whereas less than 30 species are symbiotic (zooxanthellate) or facultative (apozooxanthellate) species. This paper includes 35 species (20 genera) of caryophylliids present in soft and hard bottoms of Colombian seas, which have been mainly collected through INVEMAR expeditions (between 10 and 500 m depth) during the last 10 years. Two new species are described, Stephanocyathus isabellae and Heterocyathus antoniae, the latter belonging to a genus previously known only from the Indian and Pacific oceans.